Gluon Amplitudes at Two Loops in \(\mathcal{N}\) = 2 SCQCD - Leoni, Marta; Mauri, Andrea; Santambrogio, Alberto (Mathematics and Computer Science: Contemporary Developments Vol. 4, 2024)
We compute the four-point amplitude with external adjoint particles in \(\mathcal{N}\) = 2 SCQCD at two loops using \(\mathcal{N}\) = 1 superspace Feynman diagrams. We consider the diagrammatic difference with the corresponding process of \(\mathcal{N}\) = 4 SYM finding a nonvanishing result, which is a nontrivial function of the kinematic variables. This demonstrates that in \(\mathcal{N}\) = 2 SCQCD, even in the sector with external particles in the vector multiplet, the amplitude/Wilson loop duality is inevitably broken at two loops. Moreover, our result does not exhibit uniform transcendentality weight, meaning that in the adjoint sector of \(\mathcal{N}\) = 2 SCQCD the maximum transcendentality principle is violated.